Evaluation of tribological characteristics of biodiesel based on rapeseed oil and its blends with mineral diesel fuel - Бойченко, С.В.; Криворотько, В.М.; Голубов, О.С. (Proceedings of National Aviation University (archive), 2007)
Research results on ШХ15 steel wearing capacity when sliding motion in biodiesel fuel on the basis of rape, mineral diesel fuel and their mixture, are presented. It was established that biodiesel fuel and its mixtures with mineral diesel fuel have better antiscuff but worse antiwear properties than pure mineral diesel fuel. This fact tells us about the possibility of optimal correlations of diesel and biodiesel fuel in mixture that can be used as motor fuel for autotransport means equipped with diesel engines.